Pyridoxal Phosphate vs Pyridoxine for Intractable Seizures - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2005)
The efficacy of pyridoxal phosphate (PLP) compared to pyridoxine (PN) in the control of idiopathic intractable epilepsy was studied in 94 children, aged 8 months to 15 years, at the National Taiwan University Hospital, Taipei, Taiwan.